Raging Waters China, India, Bangladesh, and Brahmaputra River Politics - Samaranayake, Nilanthi (Marine Corps University Press (MCUP), 2018)
The book aims to provide a common platform for interested parties-policy makers without training in hydrology and scientists without a background in the study of international relations-to consider the water challenges faced by Bangladesh, India, and China along the entire Brahmaputra against the backdrop of their bilateral relations. We hope this book will inform policy communities in China, India, and Bangladesh-as well as water resource specialists and academics internationally-about the interconnected aspects of the political-military situation in the Brahmaputra River basin and the potential for national water, energy, and infrastructure policies that could exacerbate interstate tensions and subnational human security conditions in the region.